2013
DOI: 10.1007/s10719-013-9511-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual profiles of free ceramide species and the constituent ceramide species of sphingomyelin and neutral glycosphingolipid and their alteration according to the sequential changes of environmental oxygen content in human colorectal cancer Caco-2 cells

Abstract: We previously performed a systematic analysis of free ceramide (Cers) species, the constituent ceramide species of sphingomyelins and neutral glycosphingolipids (NGSLs) using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry with high-energy collision-induced dissociation. As a result, distinct species differences were found among Cers, sphingomyelins and NGSLs in the kidneys. Using this method, we investigated various sphingolipid species from human colon cancer Caco-2 cells as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…1d). These findings agreed with the previous reports of tumor cells containing appreciable populations of dihydrospecies of Cers and sphingomyelins [7][8][9] and their composition were elevated under hypoxia [3,10]. (t18:0-C22:0h), and 1030.9 (t18:0-C24:0h).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1d). These findings agreed with the previous reports of tumor cells containing appreciable populations of dihydrospecies of Cers and sphingomyelins [7][8][9] and their composition were elevated under hypoxia [3,10]. (t18:0-C22:0h), and 1030.9 (t18:0-C24:0h).…”
Section: Resultssupporting
confidence: 93%
“…Sphingolipids were purified from 5×10 7 cells as previously described [3,4]. Briefly, lipids were extracted with a chloroformmethanol mixture.…”
Section: Preparations Of Cers Sphingomyelins and Gslsmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes are also affected by hypoxia, as demonstrated by Tanaka et al in human colorectal cancer cells (Caco-2) under hypoxic conditions (O 2 1%) for three days [129]. The authors showed that, in normoxia, major constituent ceramide species of neutral glycosphingolipids (NGSLs) were composed of the usual long-chain base of sphingosine (d18: 1) and hydroxy fatty acid (HFA); while, under hypoxic conditions, all the Cers, and nearly 80% of the sphingomyelins, were dihydrosphingolipids, composed of d18: 0-NFAs, but a significant proportion of d18: 1-HFAs still remained in the NGSLs [129]. …”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 95%